SISTEM INFORMASI MANAJEMEN PENYIARAN IKLAN RADIO - Berliana Kusuma Riasti; Rosita Yanuarti; Annisa Annisa; Gita Anesya Pebrianika (Universitas Sebelas Maret, 2016)
Advertising Broadcasting is the main source of revenue from radio broadcasting business. The advertiser company / agency entrusts the broadcasting of its product advertisements to radio that it believes can effectively introduce its products or services to the public. Thus the main business of the radio is to provide the advertisers with the optimal service as customers by providing confidence in their professional performance.This study discusses how to build a management information system that is intended to provide services to customers of radio advertisers to meet the demands of professional services. These needs include the accuracy of the selection of broadcasting hours for advertising a particular product or service so that the effectiveness of ad broadcasting is fulfilled, ad scheduling rapid broadcasting, easy and reliable up to the need for a disciplined performance of broadcasting ads made in accordance with the agreement contained in detail at Purchase order. The method used in this research is WaterFall Development Life Cycle System (SDLC). The first step is done in this study by conducting data collection by observation, interview and documentation study at PT. Swaramedia Pewaran (Radio Karysma FM).The results of this study is the realization of ad-based information management information system oriented to meet customer needs with system functionality such as online ad scheduling, arrangement and supervision of the broadcasting of advertisements until the presentation of reports for advertisers and management of accurate radio in the form of documentation of transactional evidence that became part Of customer advertising services.